Narrative Identity and the Redemptive Self: An Intellectual Autobiography, with Occasional Critique - McAdams, Dan P. (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2022)
In this intellectual autobiography, I trace the development of the idea of narrative identity as manifest in personality and developmental psychology. As far as my own work in this area is concerned, the story begins in the early 1980s when my students and I struggled to understand the meaning of Erik Erikson’s concept of identity. Early work on a life-story model of identity aimed to situate the concept within the rapidly transforming field of personality psychology, first articulated as an alternative to the ascending conception of the Big Five traits. Eventually, I turned my attention to the redemptive life stories told by highly generative American adults, as my understanding of narrative identity came to be more fully contextualized in culture and history. While hundreds of nomothetic, hypothesis-testing studies of narrative identity have been conducted in the past two decades, the concept has also proven useful in the realm of psychobiography, as illustrated in my case studies of the redemptive life story constructed by the American President George W. Bush, and in my research into the strange case of President Donald J. Trump, whose most striking psychological attribute may be the near total absence of a narrative identity.